The Characteristics of Sex Differentiation Based on Morphological Traits During the Early Development Stage of the Swimming Crab Portunus trituberculatus and Sex Prediction Model Comparison - Yanqing Peng; Junkai Lu; Ronghua Li; Chendong Xu; Shangbiao Zheng; Zhiming Ren; Chuan He; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes)
To investigate the morphological traits of different sexes during the early development stage of the swimming crab Portunus trituberculatus, the genetic sex of 405 crablets from stages C I–V was determined using sex-linked molecular markers. The external appearance of each crab was observed, and the morphological traits, including carapace length (CL), full carapace width (FCW), abdomen width (AW), and abdomen length (AL), were measured to compare the differences between the sexes and to develop non-intrusive methods for sex identification. The genetic sex identification demonstrated that the female-to-male sex ratio at each stage did not deviate from 1:1. The gonopores of the females were first observed at stage C I using a scanning electron microscope; however, the shape difference in the abdominal flap between the sexes from stages C I to stage C V were not observed under a dissecting microscope. Correlation analysis showed that AW3 and AW4 were significantly correlated with sex at stage C V. Three methods were used to predict the sex of the crablets according to the morphological measurements; among them, the multinomial logistic regression (MLR) model performed better than the threshold method or the stepwise discriminant analysis, and the accuracy at stage C V increased to 90% when detailed abdominal parameters were included. These results indicate that it is feasible to predict sex during the early development stages of P. trituberculatus through morphometric and geometric parameters, which would be helpful for the creation of monosex populations of this species.